2009
DOI: 10.1002/jrs.2274
|View full text |Cite
|
Sign up to set email alerts
|

Lineshape analysis of stimulated Raman spectra of the near‐nozzle region of free jet expansions

Abstract: An anomalous lineshape of stimulated Raman spectra obtained from the region very close to the nozzle of supersonic pulsed expansions of nitrogen is presented. High-resolution Raman spectra of the Q branch of the fundamental vibration mode of N 2 have been recorded from two different nitrogen expansions at T 0 = 295 K and P 0 = 1.5-3.5 bar, the lasers crossing the jet axis in the range z/D = 0.25-1.25, where D is the effective nozzle diameter. The combination of Doppler shifts and strong gradients of density an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…This is 0.42 MHz lower than the B 0 determined here and is outside the combined error bars. On the basis of a structural fit to the data of ref , Białkowska-Jaworska et al previously predicted B 0 = 4305.84(15) MHz for cyclohexane . This value is in excellent agreement with the supersonic-jet B 0 .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This is 0.42 MHz lower than the B 0 determined here and is outside the combined error bars. On the basis of a structural fit to the data of ref , Białkowska-Jaworska et al previously predicted B 0 = 4305.84(15) MHz for cyclohexane . This value is in excellent agreement with the supersonic-jet B 0 .…”
Section: Resultssupporting
confidence: 57%
“…Raman spectroscopic measurements in molecular beams have been undertaken for a number of molecules ,, including cyclohexane . The main benefit of using a molecular beam instead of a gas cell setup is the reduction of many perturbing factors .…”
Section: Introductionmentioning
confidence: 99%
“…The signals are background (noise) free, unlike in CARS, and provide natural rejection of fluorescence, which is a major problem in Raman spectroscopy. Anomalous SRS line shapes in regions very close to the nozzle of supersonic pulsed expansions of N 2 are presented by Ramos et al [137] The comparison of the experimental results with the simulation of the SRS spectrum from this spatial region provides valuable information about the near-nozzle flow field. The high-resolution SRS of the band located at 1664.16 cm −1 in C 2 H 4 was reanalyzed by the tensorial formalism developed in Dijon for X 2 Y 4 asymmetric-top molecules.…”
Section: Stimulated Raman Spectroscopymentioning
confidence: 99%
“…Nevertheless, in their collaborative efforts, Campbell and Lovas finally concluded that density and temperature gradients along the laser beam are responsible for double peaked lines [10]. Ramos et al disregarded condensation of nitrogen and attributed the observed double peak structure of lines to inhomogeneous line broadening due to strong temperature and density gradients within the silent zone, along the line of sight [11].…”
Section: Introductionmentioning
confidence: 99%